Screening castor (Ricinus communis) genotypes for salinity tolerance in terms of germination, growth and plant ion composition - RAGHAVAIAH, CV; LAVANYA, C; KUMARAN, SHAKTI; JEEVANROYAL, TJ (The Indian Journal of Agricultural Sciences, 2011)
Pot culture experiments were conducted during 2001-02 and 2002-03 at the Directorate of Oilseeds Research, Hyderabad to evaluate 20 genotypes of castor (’DCS 89’, ’481’, ’DCH 177’, ’VP 1’, ’GC-2’, ’LRES 17’, ’DCS9’, ’DCS86’, ’GCH 5’ ’DeS 33’, ’TMV 5’, ’TMV 6’, ’DCH 149’, ’DPC9’, DCH 151" ’GCH4’, ’DCS5’, ’Aruna’, ’DCH32’and ’Kranti’) under 4 levels of salinity ( ECe <2,4,6,8 dS/m) in a completely randomized design with 3 replications. It was found that with increase in the level of salinity from <2 to 8 dS/m there was distinct reduction in the seed germination, growth parameters, like shoot growth and its dry weight ,root growth and its dry weight and relative water content of plant. There was an increase in plant Na/K ratio and decrease in plant Ca/Na ratio in response to increased level of salinity of the soil medium. Among the test genotypes considering various parameters ’481’, ’DCH 151’, ’DCH 149’, ’DCH32’, ’DCS86’, ’TMV6’,’DPC 9’, ’DeS 82’ and ’GC 2’ exhibited better tolerance to salinity than the rest of the genotypes.